2020
DOI: 10.18203/2319-2003.ijbcp20205124
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on assessment of risk factors and impact of patient counselling in health-related quality of life of patients with coronary artery diseases

Abstract: Background: Cardiovascular disease is the most frequent cause of morbidity and mortality throughout the world. The aim of the study was to determine assessment of risk factors and impact of patient counseling in health-related quality of life of the patient.Method: This was a prospective observational study conducted in the department of cardiology. A suitably designed standard SF-36 questionnaire was given to all patients enrolled in the study before and after counseling. All information relevant to the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Doctors gave therapy to 94 percent of patients at the time of their illness. In this study indicated that patients had good perception about all risk factors except stress and sedentary life style [7].…”
Section: Discussionmentioning
confidence: 58%
“…Doctors gave therapy to 94 percent of patients at the time of their illness. In this study indicated that patients had good perception about all risk factors except stress and sedentary life style [7].…”
Section: Discussionmentioning
confidence: 58%